2008
DOI: 10.1144/1470-9236/07-036
|View full text |Cite
|
Sign up to set email alerts
|

Use of municipal solid waste incinerator bottom ash as aggregate in concrete

Abstract: As a result of their chemical and mineralogical characteristics, bottom ashes from municipal solid waste incinerators can, in principle, be used as aggregates in the production of normal strength concrete. However, because the ashes contain concrete-damaging components, such as chlorides, sulphates and organic compounds, or excessive quantities of fines, aluminium and waste glass, recycling becomes problematic. In particular, inclusions of aluminium in the ash particles and a glass content of about 15% cause c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 7 publications
1
18
0
1
Order By: Relevance
“…Due to the relatively minor environmental impact expected when MSWI bottom ash is used with construction materials, a number of research studies have been conducted on the use of bottom ash in road construction (Bruder-Hubscher et al, 2001;Forteza et al, 2004;Izquierdo et al, 2001;Lucido and Wilson, 2002) and in concrete (Bertolini et al, 2004;Jurič et al, 2006;Keppert et al, 2012;Müller and Rübner, 2006;Rubner et al, 2008). Efforts have focused on the use of bottom ash as a replacement for aggregate or cement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the relatively minor environmental impact expected when MSWI bottom ash is used with construction materials, a number of research studies have been conducted on the use of bottom ash in road construction (Bruder-Hubscher et al, 2001;Forteza et al, 2004;Izquierdo et al, 2001;Lucido and Wilson, 2002) and in concrete (Bertolini et al, 2004;Jurič et al, 2006;Keppert et al, 2012;Müller and Rübner, 2006;Rubner et al, 2008). Efforts have focused on the use of bottom ash as a replacement for aggregate or cement.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike successful applications of other recycled materials in concrete such as recycled aggregate concrete (Gökçe and Ş imşek, 2013;Saravanakumar and Dhinakaran, 2014), coal fly ash (Gao et al, 2013;Wang, 2013) and others (Ahmadi et al, 2014;Ferreira et al, 2014;Kwan et al, 2013), not many successful uses of ash addition have been reported. This is mainly due to the side effect caused by the chemical reaction of aluminium in a high alkaline environment (Aubert et al, 2004;Bertolini et al, 2004;Müller and Rübner, 2006;Rubner et al, 2008). The presence of metallic aluminium in bottom ash causes an evolution of hydrogen gas and the gas is entrapped within concrete by the following chemical reaction (Aubert et al, 2004;Müller and Rübner, 2006;Sorlini et al, 2011) 2Al þ 4OH À þ 2H 2 O !…”
Section: Introductionmentioning
confidence: 99%
“…Incluso se han incorporado como aditivos al hormigón residuos provenientes de la industria del automóvil (6), elementos de circuitos electró-nicos (7,8), y otros tipos de residuos, incluso de origen orgánico (9,10). En definitiva la búsqueda de un "hormigón verde" como lo definen Damtoft (11) y C. Meyer (12) capaz de actuar como catalizador para poner de nuevo en servicio residuos generados por la actividad humana.…”
Section: Antecedentesunclassified
“…To reduce the release of pollutants, many processes are proposed: the natural weathering of bottom ash (for about 2 months) to promote the carbonation (that involves the absorption of CO 2 , which causes pH decrease and improvement in leaching properties) [24]; different methods to perform an accelerated carbonation [25,26]; the washing of residues with water [18,27] or with chemical solutions [8,28]; the vitrification (at 1450°C) and subsequent crushing of residues [29].…”
Section: Introductionmentioning
confidence: 99%